PERSONAL DEVELOPMENT AND SELF-MANAGEMENT PROBLEMS IN THE PROCESS OF EDUCATIONAL ACTIVITY IN MILITARY ACADEMIC LYCEUMS - Ergashev Doniyor (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article analyzes the main psychological problems affecting the formation of students’ personal development and self-management competencies in the process of educational activity in military academic lyceums (“Temurbeklar Maktabi”). The study employed methods such as theoretical analysis, review of scientific literature, psychological observation, and analysis of military-pedagogical documents.The findings revealed that strict military discipline, external control, stress, and contradictions between collectivism and individual identity significantly influence students’ internal autonomy and self-management abilities. Developing stress resilience, reflection, and intrinsic motivation plays an important role in overcoming these challenges.